Unmet need for contraception in South Asia: Levels, trends and determinants - Rafiqul Huda Chaudhury (Asia-Pacific Population Journal, 2001)
“Unmet need for family planning”, which refers to the condition of wanting to avoid or postpone childbearing but not using any method of contraception, has been a core concept in international population for more than three decades (Casterline and Sinding, 2000; Freedman, 1987). The importance of the unmet need for family planning or satisfying an individual’s reproductive aspirations as a rationale for formulating population programmes was further explicitly reiterated by the Programme of Action of the International Conference on Population and Development (ICPD), which states that “Government goals for family planning should be defined in terms of unmet needs for information and services” and that “all countries should, over the next several years, assess the extent of national unmet need for good-quality family planning services (United Nations, 1994). ICPD+5 has called for a 50 per cent reduction in the unmet need for contraception by 2005 and its total reduction by 2015.